A retrospective descriptive review of children diagnosed with Henoch Schönlein purpura at Red Cross War Memorial Children's Hospital over a 5-year period (2015-2019) - Makhewarene, Mpho Melinkhov (Department of Paediatrics and Child Health, 2026)
Background: IgA vasculitis, formerly known as Henoch-Schönlein Purpura, is the most common primary vasculitis in childhood. The prevalence, variation in clinical features, and outcomes of IgA vasculitis in low-to-middle income countries are poorly understood, due to a lack of published research. This study aimed to provide a comprehensive description of IgA vasculitis cases encountered at a South African children's hospital. Methods: A retrospective folder review of all children with a discharge diagnosis of IgA vasculitis at (RCWMCH) a tertiary children's hospital between January 2015 and December 2019 was performed. Patient demographics, clinical characteristics, laboratory findings, management and short-term outcomes were summarised; conventional descriptive and inferential statistical methods were used to analyse the dataset. Results: Forty-nine children were eligible for inclusion in the analysis, mean age was 6 years and 5 months, male-to-female ratio was 1:1. Rash was the presenting symptom in 48 (97%) children; arthralgia 41 (84%), abdominal pain 18 (37%); oedema manifested as scrotal oedema in 1 (2%) and angioedema in three (6%) children. Kidney involvement was evident in twenty-five (51%) children with proteinuria and or haematuria, while isolated microscopic haematuria occurred in six (12%). Complications were infrequent, five (10%) patients had IgA nephritis on biopsy and one (2%) had a gastrointestinal bleed. The mean length of hospital stay was 1.6 (SD 2) days. At one year of followup, two (4%) children had persistent proteinuria and only one patient (2%) still had haematuria. Conclusion: The clinical course of IgA vasculitis in this cohort of South African children was mostly self-limiting, consistent with international literature. However, patients with persistent haematuria or proteinuria require longer-term follow-up. Collaborative studies within South Africa and subSaharan Africa may provide a more accurate picture of the epidemiology of childhood HSP and its complication rates.